2001
DOI: 10.1002/glia.1051
|View full text |Cite
|
Sign up to set email alerts
|

Isolated human astrocytes are not susceptible to infection by M‐ and T‐tropic HIV‐1 strains despite functional expression of the chemokine receptors CCR5 and CXCR4

Abstract: Within the brain, HIV-1 targets the microglia and astrocytes. Previous studies have reported that viral entry into astrocytes is independent of CD4, in contrast to microglia. We aimed to determine whether chemokine receptors play a role in mediating CD4-independent HIV-1 entry into astrocytes. We found that embryonic astrocytes and microglial cells express CCR5, CCR3, and CXCR4 transcripts. Intracellular calcium levels in astrocytes were found to increase following application of RANTES, MIP-1beta (CCR5-agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 67 publications
(41 reference statements)
2
35
1
Order By: Relevance
“…Astrocytes do not usually express CD4 and therefore support only an inefficient infection by particular HIV-1 strains (56,74). The chemokine receptor expression profile of astrocytes is controversial, and the role of coreceptors in the observed low-level infection is unclear (8,56). In order to determine if the cultured fetal and adult GFAP-positive cultures express functional coreceptors, we used an Ad-CD4 vector to express CD4 on these cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytes do not usually express CD4 and therefore support only an inefficient infection by particular HIV-1 strains (56,74). The chemokine receptor expression profile of astrocytes is controversial, and the role of coreceptors in the observed low-level infection is unclear (8,56). In order to determine if the cultured fetal and adult GFAP-positive cultures express functional coreceptors, we used an Ad-CD4 vector to express CD4 on these cells.…”
Section: Resultsmentioning
confidence: 99%
“…These ligands each bind several chemokine receptors (CCR1, CCR3, CCR5, and CCR9 for RANTES and CCR3 and D6 for eotaxin), indicating a role for this subclass of receptor in the infection of astrocytes. Although CCR5 expression was not detected on these astrocytes, several groups have reported expression on astrocytes in situ in the brain, which is lost rapidly in culture (8,29,44). The lack of inhibition by the CCR5 small-molecule inhibitor TAK-779, as well as by the CCR5-specific MAb 2D7, confirms that the weak inhibition by RANTES was not due to the presence of low levels of CCR5.…”
Section: Fig 4 Infection Of Cd4mentioning
confidence: 95%
“…Given that, in primary fetal astrocytes, IFN-␥ did not induce the expression of any of the HIV receptors that we evaluated, the mechanism by which IFN-␥ can induce HIV replication in primary astrocytes may be at postentry events, perhaps by inducing key transcriptional factors in astrocytes. Taken together, our data show that the presence of IFN-␥, and possibly other soluble factors found in the CNS milieu in vivo, may account for the discrepancy between postmortem data identifying viral transcripts within astrocytes (2) and in vitro studies demonstrating astrocytes to be resistant to HIV infection (4,12). The finding that astrocytes are productively infected with HIV is significant because astrocytes make up approximately 50%, while microglia make up 10 to 20%, of the CNS cell population (18,31).…”
Section: Fig 2 Cytokine Receptor Expression On Astrocytes U87mg Cementioning
confidence: 86%
“…Recently, using laser capture microdissection, HIV p24 was reported to occur in astrocytes in the basal gangliae and frontal cortexes of HIV ϩ individuals (30). Conversely, in vitro infectivity studies of astrocytes have demonstrated either minimal HIV output or latent/nonproductive HIV infection (4,11,20,24,29). The discrepancy between in vitro and postmortem studies suggests that a factor(s) in the central nervous system (CNS) milieu may augment the HIV infection of astrocytes.…”
mentioning
confidence: 99%
“…Indeed, there is ample evidence that these receptors are not always sufficient for viral infection. Further examples include human CD4-negative astrocytes that express functional CCR5 and CXCR4 and are resistant to infection by HIV-1 strains (Boutet et al, 2001) and CD4 + CXCR4 + cells, also resistant to infection with HIV-1 (Moriuchi et al, 1997). This was shown by infecting U937 monocyte-derived cell lines that were shown to be either permissive or nonpermissive for infection by HIV-1.…”
Section: Hiv Infection Of Cd4 Negative Cellsmentioning
confidence: 99%